OP0024 Drug trough levels and antidrug antibodies in nonselected ankylosing spondylitis patients using self-injected antitnf drugs. (15th June 2017) - Hiltunen, J; Parmanne, P; Sokka-Isler, T; Lamberg, T; Kaipiainen-Seppänen, O; Isomäki, P; Kauppi, M; Pirilä, L; Uutela, T; Tuompo, R; Relas, H; Yli-Kerttula, T; et al.
Abstract : Background: Immunization to biological drugs can reduce the treatment efficacy and increase the risk of adverse events. Objectives: To determine the drug trough concentrations and anti-drug antibody (ADAb) levels of self-injected TNF-inhibitors, in non-selected patients with ankylosing spondylitis (AS) attending the rheumatological outpatient clinic, and to study the patient related factors affecting the immunization to antiTNF drugs. Methods: A total of 313 patients with AS were recruited. A blood sample, taken 1–2 days prior to next drug injection, was obtained from 273 patients. Trough concentration of the anti-TNF drugs were measured with capture-ELISA (Promonitor EIA, Progenica), the levels of ADAb with radioimmunoassay (Sanquin Laboratories, The Netherlands), and the serum TNF-blocking capacity by using an in-house reporter gene assay. The clinical activity of AS was assessed using the Bath AS Disease Activity Index (BASDAI), the Bath AS Functional Index (BASFI), and the Maastricht AS Entheses Score (MASES). Results: ADAbs were observed in 21% of patients on adalimumab (n=99), in 0% of those on etanercept (n=83), in 3% of those on golimumab (n=79) and in 50% of those on certolizumab pegol (n=12). The BASDAI in ADAb positive patients was 1.4 (sd 1.4) and in the ADAb negative patients 2.0 (sd 1.8 p=0.060). Factors affecting the immunization to biological drug could be further analyzed in patients using adalimumab. Trough drug concentrations of adalimumab correlated with the presence of ADAb (r=-0.54, rp<0.0001). In adalimumab users higher BMI was associated with the presence ADAb (p=0.019, adjusted for gender, age, and the time of biological use). Of patients who used methotrexate (MTX) 12% were ADAb positive and of those who did not use MTX 28% were ADAb positive (p=0.048 adjusted for gender, age, weight, and the time of biological use). The use of sulphasalazine was not associated with lower number of ADAb positive patients. Of adalimumab users with ADAb+ the mean BASDAI was 1.2 (sd 1.4) and of those without ADAb 1.9 (sd 1.9) (p=0.091). Of adalimumab users the drug concentration was in the target range (5–10 mg/l) in only 33% of patients. Conclusions: The disease activity of AS patients using self injected antiTNF drugs was low. The immunization to adalimumab was relatively common in nonselected AS patient population. However, no clear association was observed between the presense of ADAb and the disease activity. Acknowledgements: The study was financially supported by Pfizer Disclosure of Interest: J. Hiltunen: None declared, P. Parmanne: None declared, T. Sokka-Isler: None declared, T. Lamberg: None declared, O. Kaipiainen-Seppänen: None declared, P. Isomäki: None declared, M. Kauppi: None declared, L. Pirilä: None declared, T. Uutela: None declared, R. Tuompo: None declared, H. Relas: None declared, T. Yli-Kerttula: None declared, H. Valleala: None declared, M. Romu: None declared, T. Rannio: None declared, K. Paalanen: None declared, A. Juha: None declared, P. Ekman: None declared, K. Tadesse: None declared, J. Borodina: None declared, P. Elfving: None declared, R. Peltomaa: None declared, M. Leirisalo-repo: None declared, H. Kautiainen: None declared, S. Jokiranta: None declared, K. Eklund Grant/research support from: Pfizer has supported the study financially, Consultant for: Advisory board meetings BMS, MSD, Pfizer, Abbvie, Speakers bureau: Lectures: BMS, Roche, Pfizer, Novartis